Entrusting coast guards with maritime law enforcement powers: lessons for Malaysia - Hamid, Abdul Ghafur@Khin Maung Sein; Mustafa, Maizatun; Su Wai Mon@, Faridah (International Islamic University Malaysia, 2016)
In view of many and varied maritime threats and the growing number of maritime crimes, it is necessary for States to have coast guards with maritime law enforcement powers to secure their maritime territories and protect maritime interests. Modern coast guards play a crucial role in sustaining maritime security and their operations have become more and more sophisticated. However, in the case of the Malaysian Maritime Enforcement Agency (MMEA), commonly known as the Malaysian Coast Guard, it is found that it is still struggling even after twelve years of its establishment to achieve its primary objective of becoming a single maritime law enforcement agency in Malaysia. The present study finds that there seems to be a veiled competition between the MMEA on one side, and the other law enforcement bodies on the other. An analysis of the practice of coast guards of the USA, India and Japan is made to find a solution to this crucial issue revolving around Malaysia’s maritime security. The study finally concludes that the controversial section 7(3) of the MMEA Act should be amended to clearly entrust the MMEA with, and exclude other relevant agencies from, maritime law enforcement powers in the Malaysian maritime zones.